Risk scoring and prediction of early onset septicaemia in neonates through study of perinatal factors - Sharma, Deepika; Batham, Ashish (International Journal of Contemporary Pediatrics, 2018)
Background: Diagnosis of early onset septicaemia is often difficult due to lack of specificity of clinical manifestations. Being a common but neglected problem, the present study was undertaken to develop a scoring system which can predict early neonatal septicemia. Methods: 300 newborns born out of consecutive deliveries were assessed for the total score as combination of physical factors and neuromuscular factors. Information for perinatal factors was collected on a prepared pro forma by questionnaire method. Data was tabulated and subjected to statistical analysis. Results: Incidence of neonatal infection was higher in the presence of birth asphyxia, unclean vaginal examination, presence of foul smelling vaginal discharge, or when duration of labour exceeded 24 hours as compared to prolonged rupture of membranes. Incidence of infections among babies born before 37 weeks gestation or having a birth weight of 2 kg or less was nearly the same as in the cases of premature rupture of membranes (PROM). 224 cases got score 0-3 and only 0.6% got infected, whereas out of 62 cases with score 4-5, 51.6% were infected and 14 out of 14 having score of 6 or more had infection. The sensitivity of scoring system was 96%, specificity 90%, positive predictive value of 88% and negative predictive value of 60.5%. Conclusions: Besides PROM there are many other perinatal factors which are of significance in relation to early onset infections. This led to the formulation of the presenting scoring system. Validation of this scoring system through further studies can help in early diagnosis, administration of proper antibiotics and inhibition of the irrational use of antibiotics.